THE IMPACT OF QUALITY OF PREPAID ELECTRICITY SERVICE AND EMPLOYEE’S PERFORMANCE ON CUSTOMER’S SATISFACTION IN PT. PLN (PERSERO) GORONTALO, AREA OF TELAGA - Endi Rahman (AIBPM Publisher, 2019)
The purpose of this study is to see whether PT PLN (Persero) Gorontalo Area of Telaga is concerned with the quality of prepaid electricity service and employee performance simultaneously in providing satisfaction to its customers. The Synergy between the products (prepaid electricity services) and employee’s performance can provides best service to customers. The method used in this research is an associative research causal, namely research that reveals problems and examines the relationship or influence of two or more. While causal research is research whose relationship has an influence between two or more variables. The Analysis of research data was using validity and reliability tests and multiple regression tests, multiple correlation tests, hypothesis tests and multiple determination tests. By the results of the analysis through questionnaires processed using the SPSS application, it can be concluded that the quality of prepaid electricity services and employee’s performance has an influences on customer satisfaction. The conclusions that drawn by the research has been done with the quality of prepaid electricity service and employee’s performance have a significant influences on customer satisfaction in PT. PLN (Persero) Gorontalo, Area of Telaga.